Mathematics Education in a Context of Inequity, Poverty and Language Diversity : Giving Direction and Advancing the Field - Phakeng, Mamokgethi Setati, 1966-; Lerman, S. (Springer Nature, 2016)
This volume is dedicated to the career of Jill Adler and the role she has played in growing mathematics education research in South Africa, Africa and beyond. Her work epitomises what is referred to as the 'engaged scholar': i.e. doing rigorous and theoretically rich research at the cutting edge of international work in the field which at the same time contributes to critical areas of local and regional need in education. Jill is one of the world's leading experts in mathematics education research and her exemplary career is a continuous source of inspiration for generations of researchers and students. The chapters in this volume are authored by Jill's former PhD students, a few select colleagues from different parts of the world that she collaborated with as well as leading scholars who she worked with in PME, ICMI and in her many international assignments. In essence, this volume celebrates Jill's contribution not only to mathematics education but also to our contributions as her friends and colleagues. Topics covered include language and mathematics, teacher education, and the dilemma of an activist researcher engaging in issues that matter hugely to the participants in the research, students and teachers in post-apartheid schooling, whilst also setting up the separation that is needed for good research.